Urgensitas Nilai Pendidikan Karakter Perspektif Ta’limul Muta’allim dalam Menghadapi Krisis Moral - Irfan Jauhari (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Moral decadence becomes a problem that cannot be taken lightly, which in turn becomes a crisis that permeates all segments of life and layers of society, including the education segment. The current state of education, if observed, is increasingly apprehensive, so it requires an appropriate solution to overcome it. To go towards holistic character education and to arrive at the goal of character education, it must not be separated from the principles of character education. Because the principle is the most fundamental and the main thing, the thing that cannot be absent in action. The principle is the spirit of a development or change, and is the accumulation of experience and meaning by a particular object or subject. To achieve the success of character education is indeed not easy, it requires a structured and intense process of education and coaching. According to Az-Zarnuji in our ta'limul muta’lim, the process starts from the structuring of the heart to the intentions, goals, etiquette in learning and its application in life so that it becomes a person of character.